2020
DOI: 10.1002/ima.22486
|View full text |Cite
|
Sign up to set email alerts
|

Detection and classification of electroencephalogram signals for epilepsy disease using machine learning methods

Abstract: The electroencephalogram (EEG) signal plays a key role in the diagnosis of epilepsy. This study describes an automated classification of EEG signal for the detection of Epilepsy disease using soft computing methods. The proposed method is comprised of three modules: (a) transformation, (b) feature computation, and (c) feature classifications. In the first module, the nonsubsampled contourlet transform is applied on the EEG signal which decomposes the signal into approximate and directional subbands. The decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The highest accuracy result achieved was 94% for KNN, while the DT and SVM obtained the same accuracy of 88%. Whereas [21], used EEG signal to classify two epileptic seizures (focal and non-focal) by using four types of feature techniques using probability density function (PDF), energy and pattern spectrum entropy (PSE), mutual information (MI), and characteristic feature vector (CFR). Further, the outcome of feature techniques used as input for the adaptive neurofuzzy inference system classification technique, which is a kind of artificial neural network (ANN).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The highest accuracy result achieved was 94% for KNN, while the DT and SVM obtained the same accuracy of 88%. Whereas [21], used EEG signal to classify two epileptic seizures (focal and non-focal) by using four types of feature techniques using probability density function (PDF), energy and pattern spectrum entropy (PSE), mutual information (MI), and characteristic feature vector (CFR). Further, the outcome of feature techniques used as input for the adaptive neurofuzzy inference system classification technique, which is a kind of artificial neural network (ANN).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, ANN, FIS, and ANFIS output 92.3, 88, and 96%, respectively. A paper by (Srinath & Gayathri, 2021) carried out classification using soft computing methods along with ANFIS algorithm which results in an accuracy of 99.4%.…”
Section: Deep Neural Networkmentioning
confidence: 99%
“…The model improved the robustness of ANFIS technique and amplified the classification accuracy results. Furthermore, [91] implemented ANFIS for data classification with the accuracy of 99.4%, specificity, and sensitivity of 99.7%. Table 8 shows the list of papers which utilized NF for in their proposed classification model.…”
Section: Exclusion Criteria Inclusion Criteriamentioning
confidence: 99%
“…The observations suggested that the fine Gaussian SVM was most efficient. Classification of the EEG signals into focal and non-focal signals using soft computing methods was performed in [132]. The whole process comprises three modules: transformation, feature computation, and feature classifications.…”
Section: ) Ml-based Approaches In Epilepsy Diagnosismentioning
confidence: 99%